Correlation between Cognitive Function and Physical Performance in Community-Dwelling Older Adults - Amanda Risviandari; Rensa Rensa (Althea Medical Journal, 2021)
Background: One of the health problems often found among older adults in Indonesia is cognitive impairment, resulting in difficulties daily life and a significant decrease in functional status. This study aimed to determine the correlation between cognitive function and physical performance in community-dwelling older adults.Methods: This was a cross-sectional study conducted from October–November 2019. Samples were collected from North Jakarta through consecutive sampling (n=38). Cognitive function was measured using the Mini-Mental State Examination (MMSE) and the physical performance was measured using the Timed Up and Go Test (TUG) method. The statistical test applied in this study was Spearman’s rank correlation (p<0.05). Results: The majority of the subjects in this study were mostly female young older adults with the most received ≥12 years of education. The results for both MMSE and TUG were normal. There was a negative correlation between MMSE and TUG scores (r= -0.357, p=0.028).Conclusions: There is a weak but significant correlation between cognitive function and physical performance in community-dwelling older adults. A further study exploring cognitive dysfunction and physical performance in older adults is needed.